Determinant interests Buy Online at UMKM Based2, C2C and O2O - Adelia Erviana Wayansari (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The Development Of Technology Causes Society To Not Be Separated From Technology, One Of Thamecommerce. Many Online Shopping Stores Have Strues Sprung Up, Making People Frequent Online Purchases. This Study Aims To Analyze Wherte Is In Ansf Infulence Stude, Security, And Proad Only Breing Interest In Micro,Small And Medium Enterprises (Smes). More Specifically, This Study Explores Method-Based Buying And Selling Transactionsbusiness To Consumer (B2C), Customer To Customer (C2C), And Online To Offline (O2O). This Type Of Research Is Quantitative. The Sampling Technique Used Non-Probability Methods, Namely Purposive Sampling Of 178 Respondents By Distributing Questionnaires Using Form. The Population In This Study Were Online Buyers Of Msmes Who Made Purchase Transctionsing The B2C, C2C, And O2O Methods. Data Analysis Using Multiple Regression Analysis Method. The Results Indicate That In Influencing Consumer Purchase Interest Online There Are A Several Considerations, Namely The Factor Of Trust, Security And Price.Pricevariable Is The Main Detenant That Influences Consumer Buying Interate Online.